Sacred cyberspaces: catholicism, new media, and the religious experience - Golan, Oren (Advancing Studies in Religion, 2022)
Every contemporary institution has had to confront the ever-evolving technologies of the digital age. Focusing on the Catholic Church, Sacred Cyberspaces reveals how old conflicts over power, influence, and legitimacy within religious organizations unfold on the internet, shedding light on the future of religious life in the new millennium.